Cannabis Unveiled: An Exploration of Marijuana's History, Active Compounds, Effects, Benefits, and Risks on Human Health - Khaled M Hasan (SAGE Publishing, 2023)
Marijuana, also known as cannabis, is a psychoactive drug that comes from the Cannabis plant. Marijuana can be smoked, vaporized, or consumed through edibles in a variety of ways. Perception changes, changes in mood, and problems with coordination are all possible side effects. Marijuana is used for both recreational and medical purposes to treat a variety of health conditions. The literature review on the effects of marijuana on the human body has increased in recent years as more states legalize its use. It is important to investigate the benefits and harmful effects of marijuana on individuals due to the widespread use of cannabis-derived substances like marijuana for medical, recreational, and combined purposes. The paper will review different aspects of marijuana in 4 main domains. A thorough discussion of marijuana's definition, history, mechanism of action, pharmacokinetics, and effects on human cells will be given in the first domain. The second domain will concentrate on marijuana's negative effects, while the third domain will look at marijuana's possible positive impacts, such as its usage in controlling multiple sclerosis, treating obesity, lowering social anxiety, and managing pain. The fourth domain will concentrate on marijuana's effects on anxiety, educational attainment, and social consequences. Additionally, this paper also will provide a highlight of the history of marijuana use and governmental legislation, both of which play a significant role in determining how the public views marijuana. In conclusion, this paper provides a comprehensive review of marijuana's effects, which may be of interest to a large readership. This review adds to the continuing discussion about the use of marijuana by analyzing the data that is currently available about the possible advantages and disadvantages of marijuana usage.